A central amygdala input to the dorsal vagal complex controls gastric motility in mice under restraint stress - Wang, Hao; Liu, Wen-Jian; Wang, Xi-Yang; Chen, Xiao-Qi; Cai, Rong-Lin; Zhang, Meng-Ting; Wang, Hai-Tao; He, Guang-Wei; Zhang, Zhi; Shen, Guo-Ming (Frontiers in Physiology, 2023)
Abstract Background/aims Psychological and physiological stress can cause gastrointestinal motility disorders. Acupuncture has a benign regulatory effect on gastrointestinal motility. However, the mechanisms underlying these processes remain unclear. Methods Herein, we established a gastric motility disorder (GMD) model in the context of restraint stress (RS) and irregular feeding. The activity of emotional center - central amygdala (CeA) GABAergic neurons and gastrointestinal center - dorsal vagal complex (DVC) neurons were recorded by electrophysiology. Virus tracing and patch clamp analysis of the anatomical and functional connection between the CeAGABA → DVC pathways were performed. Optogenetics inhibiting or activating CeAGABA neurons or the CeAGABA → DVC pathway were used to detect changes in gastric function. Results We found that RS induced delayed gastric emptying and decreased gastric motility and food intake. Simultaneously, RS activated CeA GABAergic neurons, inhibiting DVC neurons, with electroacupuncture (EA) reversing this phenomenon. In addition, we identified an inhibitory pathway in which CeA GABAergic neurons project into the DVC. Furthermore, the use of optogenetic approaches inhibited CeAGABA neurons and the CeAGABA → DVC pathway in GMD mice, which enhanced gastric movement and gastric emptying, whereas activation of the CeAGABA and CeAGABA → DVC pathway mimicked the symptoms of weakened gastric movement and delayed gastric emptying in naïve mice. Conclusions Our findings indicate that the CeAGABA → DVC pathway may be involved in regulating gastric dysmotility under restraint stress conditions, and partially reveals the mechanism of EA. Keywords: Central amygdala; Dorsal vagal complex; Neural circuit; Gastric motility disorder; Electroacupuncture